En construcción o en viaje: apuntes sobre la representación de la identidad latinoamericana en la narrativa contemporánea - Nina Pluta (Ksiegarnia Akademicka Publishing, 2021)
Travelling or in construction: notes about the representation of the identity in the contemporary Spanish‑American fiction